Ecotourism regions of Chhattisgarh and its effect on wildlife - Rita Luka2, Dr. V.K.Joshi1*, (Journal of Experimental Sciences, 2011)
<p class="MsoNormal" style="text-indent: 0in; margin: 0in 34.3pt 0pt 35.4pt; mso-char-indent-count: 0; mso-margin-top-alt: auto; mso-margin-bottom-alt: auto; mso-para-margin-right: 34.3pt; mso-para-margin-left: 3.54gd;">Ecotourism is a major industry in developing nations. However, its impact on wildlife and indigenous people has become a controversial issue. Ecotourism is: "Responsible travel to natural areas that conserves the environment and improves the well-being of local people." (TIES, 1990). Chhattisgarh is one of the greenest states of India with over 44 % of its total area under lush forests. Chhattisgarh Eco Tourism encompasses a total of eleven wildlife sanctuaries and three national parks. The eco tourism regions of Chhattisgarh are Bilaspur-Achanakmar, Raipur-Turturia and Jagdalpur-Kanger Valley. Having a green stretch of forests land of 44% of the total geographical space, Chhattisgarh encourages eco tourism through protection and preservation of near extinct species of animals and their habitat.Indrawati National Park, Kangerghati National Park, Barnawapur Sanctuary, Sita Nadi Sanctuary Sanjay National Park and Udanti Sanctuary are the prominent eco tourism destinations in Chhattisgarh. These wildlife sanctuaries and national parks are home to the state animal (wild buffalo) and state bird (the mocking hill myna) and other endangered species of animals and birds such as spotted deer, four horned antelope, sloth bear, wild boar, wild dog, jackal, wolf, hyena and bison.